2022
DOI: 10.1021/acs.iecr.1c03891
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Solvent Effects on Homogeneity and Kinetics of the Hydroaminomethylation: A Thermodynamic Approach Using PC-SAFT

Abstract: Solvents may significantly affect the phase behavior and kinetics of chemical reactions. Especially for complex reactions performed in mixtures of different solvents, it requires a high experimental effort to quantify these effects. This work focuses on a novel thermodynamic approach to predict solvent effects on both reaction rates and phase behavior. We applied this method to the homogeneously catalyzed hydroaminomethylation of 1-decene in a thermomorphic multiphase system of methanol and n-dodecane. For tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Moreover, the activity coefficient of HAc did not play a crucial role in both kinetics and equilibrium. This finding is new since previous works by Huxoll et al 3 and Pabsch et al 4 found that the solvent influence on the activity coefficient of the acid was the main driving force for slower/faster kinetics. We now see that this is not the case for the addition of CO 2 addition.…”
Section: Influence Of Co 2 On Kinetics and Equilibriummentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, the activity coefficient of HAc did not play a crucial role in both kinetics and equilibrium. This finding is new since previous works by Huxoll et al 3 and Pabsch et al 4 found that the solvent influence on the activity coefficient of the acid was the main driving force for slower/faster kinetics. We now see that this is not the case for the addition of CO 2 addition.…”
Section: Influence Of Co 2 On Kinetics and Equilibriummentioning
confidence: 55%
“…This gives rise to the importance of developing thermodynamic models to predict gas solubility in electrolyte solutions as well as to predict the kinetics and equilibria of chemical or biochemical reactions. Several equations of state (EOS) were developed in the last decades, providing a robust modeling framework for calculating the gas solubility in electrolyte solutions and predicting kinetics and equilibria of chemical or biochemical reactions. Moreover, methods were developed to describe the simultaneous occurrence of chemical reactions and phase equilibria …”
Section: Introductionmentioning
confidence: 99%
“…As it is known from literature [14,26,27] an additional solvent usually decreases kinetics of esterification reactions and reduces the equilibrium concentration of a reaction product. In this work, the activities of reacting agents a ${a}$ i at reaction equilibrium were predicted using ePC‐SAFT advanced for different conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The possible contributions (hard-chain repulsion, dispersion interaction, association, ionic interaction) calculate for the total residual Helmholtz energy by summation. Detailed information about applications can be found in the literature for, e.g., polymer systems, ,, pharmaceuticals, , ionic liquids, ,, solubility modeling, , or reaction modeling. , …”
Section: Methodsmentioning
confidence: 99%